2023
DOI: 10.3390/nu15132916
|View full text |Cite
|
Sign up to set email alerts
|

Is Extra Virgin Olive Oil the Critical Ingredient Driving the Health Benefits of a Mediterranean Diet? A Narrative Review

Abstract: Most chronic diseases are preventable with a healthy diet, although there is debate about the optimal dietary approach. Increasingly more countries are focusing on food-based guidelines rather than the traditional nutrient-based approach. Although there is good agreement on plant foods, controversy remains about the types and amounts of fats and oils. This narrative review aims to systematically summarize and evaluate the latest evidence on the protective effects of extra virgin olive oil (EVOO) on disease ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…The benefits of the Mediterranean diet are linked to various factors, with one key element being the consumption of extra virgin olive oil as the primary added fat [5]. In their narrative review, Flynn and colleagues [5] identified that the consumption of extra virgin olive oil provides superior benefits in managing clinical biomarkers, including weight management and glycemic control.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The benefits of the Mediterranean diet are linked to various factors, with one key element being the consumption of extra virgin olive oil as the primary added fat [5]. In their narrative review, Flynn and colleagues [5] identified that the consumption of extra virgin olive oil provides superior benefits in managing clinical biomarkers, including weight management and glycemic control.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of the Mediterranean diet are linked to various factors, with one key element being the consumption of extra virgin olive oil as the primary added fat [5]. In their narrative review, Flynn and colleagues [5] identified that the consumption of extra virgin olive oil provides superior benefits in managing clinical biomarkers, including weight management and glycemic control. These protective effects of extra virgin olive oil appear to be associated with its polyphenol content rather than its monounsaturated fat content, contrary to previous considerations [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, olive oil, particularly extra virgin olive oil (EVOO), has always been recognized as a symbol of the Mediterranean diet. A high consumption of EVOO, ranging from 15.3 to 23 kg per capita/year, is a staple of the Mediterranean diet and is one of the main differences from other healthy diets [10,11]. Historically, the olive tree (otherwise known as Olea europea L.) is a well-known evergreen tree in the Mediterranean basin, which is characterized by slow growth and an extremely long life expectancy, of up to 1000 years [9,10].…”
mentioning
confidence: 99%
“…This species is one of the most important trees for the Mediterranean economy, providing many commercial products, such as food, timber, and cosmetics. However, oil remains the most important product provided by Olea Europea L. [9,11].…”
mentioning
confidence: 99%